Accounting for Crypto Assets by Issuers - Bartošová, Stela Malvína; Procházka, David, 1979 říjen 10.-; Kučera, Martin; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
The diploma thesis focuses on the accounting for Crypto Assets under IFRS, specifically tokens, from the perspective of their issuer. The thesis is divided into three chapters. The first chapter focuses on regulatory aspects on a global level and then from the standpoint of EU organisations such as ESMA, SMSG, the European Commission and the European Parliament. Furthermore, this section is dedicated to the ICO process and token classification. The second chapter focuses on token accounting under IFRS standards. Due to the lack of regulation at the time of writing the thesis, the thesis is here dedicated to mapping current requirements and relevant recommendations and their possible application to issued tokens. The last, third part, is practically oriented to examine the financial statements of selected companies and find out what approach these issuers have taken in accounting for tokens.
Vedoucí práce: David Procházka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor dipl. práce]; diplomové práce; master's theses